(3JQLeI GdaUhd GdfUjQjIs - (3GdLQLGfj GdGSJQGHGPj GdMdj, Qcf GdOjf GdLQLGfj, eMeO Hf Ydj Hf eMeO GdLQLGfj, cGf MjG (B697(3g` (B1298(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GeG HYO MeO GdhGLH hLhOg (B... (3hgj ehVhYI Ydi CQHYI aUhd, GdaUd GdChd, aj GdJhMjO, CUd cd ef COQc TjFG dGHO Cf jOQc hLhOgs
(3BNQgG (B:s
(3BNQgG(B: (3hZjQ Gdecdajf jhUd Edjge CYQGV EjdGege heTGbge hjMGSH GdLejY eMGSHI MbjbI aGage hGVHW(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 536s
(3GdPQjYI, L (B4: 89(3, L (B21: 157s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds